Tunnelled peripherally inserted central catherer-how we do them - Vijayananthan, Anushya; Nawawi, Ouzreiah; Abdullah, Basri Johan Jeet (University of Malaya Medical Centre, 2017)
In the current study, we report a new technique to place a tunnelled peripherally inserted central catheter (PICC) at the upper arm of patient under real-time ultrasound-guided venipuncture using disposal equipment provided within a standard PICC set. The tunnelling of the PICC required an extra time of 5 minutes but was well tolerated by all patients involved in the study. The tunnelled PICC was applied on 50 patients and the infection rate as well its catheter dwell time were compared to another 50 patients with conventional PICC. The rate of patients who developed infection decreased from 34% for conventional PICC to 16% in tunnelled PICC patients. The central line-associated blood stream infections rate was also decreased from 4.4 per 1000 catheter-days for conventional PICC to 1.3 per 1000 catheter-days for tunnelled PICC. The mean time to infection development for tunnelled PICC (24 days) was longer than those observed with conventional PICC (19 days). Tunnelled PICC has also increased the mean catheter dwell time from 27 days (for conventional PICC) to 47 days. Tunnelling a PICC has the potential to reduce the infection rate while increase the catheter dwell time. © 2018, Faculty of Medicine, University of Malaya. All rights reserved.